Micellar Liquid Chromatographic Determination of Carbaryl and 1-Naphthol in Water, Soil, and Vegetables - Mei-Liang Chin-Chen; Maria Rambla-Alegre; Abhilasha Durgbanshi; Devasish Bose; Sandeep K. Mourya; Josep Esteve-Romero; Samuel Carda-Broch (International Journal of Analytical Chemistry)
A liquid chromatographic procedure has been developed for the determination of carbaryl, a phenyl-N-methylcarbamate, and its main metabolite 1-naphthol, using a C18 column (250’mm’ × ’4.6’mm) with a micellar mobile phase and fluorescence detection at maximum excitation/emission wavelengths of 225/333’nm, respectively. In the optimization step, surfactants sodium dodecyl sulphate (SDS), Brij-35 and N-cetylpyridinium chloride monohydrate, and organic solvents propanol, butanol, and pentanol were considered. The selected mobile phase was 0.15’M SDS-6% (v/v)-pentanol-0.01’M NaH2PO4 buffered at pH 3. Validation studies, according to the ICH Tripartite Guideline, included linearity (r>0.999), limit of detection (5 and 18’ng mL-1, for carbaryl and 1-naphthol, resp.), and limit of quantification (15 and 50’ng mL-1, for carbaryl and 1-naphthol, resp.), with intra- and interday precisions below 1%, and robustness parameters below 3%. The results show that the procedure was adequate for the routine analysis of these two compounds in water, soil, and vegetables samples.